Brief report: The KIDSCREEN follow-up study on Health-related Quality of Life (HRQoL) in Spanish children and adolescents. Pilot test and representativeness - Palacio-Vieira, J. A. (2010)
The Spanish KIDSCREEN follow-up study reassessed the Spanish baseline sample (n=840) of the European KIDSCREEN study 3 years later (2006). The aims of this paper were to describe the KIDSCREEN follow-up study and the pilot test, and to analyze participation rates and representativeness. Instruments included the KIDSCREEN-52 HRQoL measure and a set of scales including the possible explanatory variables. Focus groups and individual interviews were carried out in a pilot test. Participants were compared with nonparticipants at baseline, and also with Eurostat census data. Twenty-two out of 24 subjects were interviewed in the pilot test. Fifteen items needed to be modified after the pilot test. Participation rate reached 54% (n = 454). Participants (mean age=12.71 years old) were on average 6 months younger than non-participants (p= 0.03), and from more educated families. KIDSCREEN follow-up instrumentation seems adequate for collecting factors with potential influence on HRQoL. Follow-up respondents’ representativeness seems to be acceptable.